Sustainable manufacturing: optimization of electrical energy consumption in plastic injection molding process - Nur Anis, Othman (2015)
This research discussed the optimization energy consumption in injection molding process to meet energy efficiency in production and get an optimal parameter setting. Injection molding is one of the techniques used in producing plastic product by injecting plastic materials molten by heat into a mold and then cooling and solidifying. It is a very complex process due to various parameters that must be considered. At this time, the industry manufacturer plastic consumes high electrical energy to produce plastic product. This in turn will release carbon dioxide gas which can have adverse effects on the environment. In this research, the allelectric injection molding machine is used because of this machine proven consume less energy compare with hydraulic and hybrid machine. Hence, this gives an advantage to the manufacturer to reduce the energy consumption from the optimization process. To optimal setting up of injection molding process, variables play a very important role in reducing electrical energy consumption to produce product. The variables involved to control settings are holding pressure, injection pressure, injection speed, mold open/close speed and screw rotation speed. Furthermore, this research presents a simple and efficient way to optimize parameter setting in injection molding process by using Taguchi experimental method and signal-to-noise ratio. With using both methods, optimal parameter settings can be achieved. In this research, an orthogonal array (OA) and signal-to-noise (S/N) ratio are employed to conduct optimization of injection molding parameter. As a result, optimization in injection molding can create the better process parameter settings which can not only reduce electrical energy consumption but, be more robust and also enhance the stability of injection process. In addition, this in turn will contribute towards sustainable manufacturing processes and reducing the carbon dioxide emissions